Social and historical factors contributing to language shift among German heritage-language migrants in Australia: An overview - Hunt, Jaime; Davis, Sacha (Linguistik Online, 2019)
Australia is a multicultural society in which over 300 different indigenous and migrant languages are spoken. While its cultural diversity is often celebrated, Australia’s linguistic diversity is still at risk due to the inherent monolingual mindset (cf. Clyne 2005) of its population. In this paper, we use a cross-disciplinary approach, drawing on both historical and sociolinguistic sources, to investigate some of the major causes of language shift among first- and subsequent generations of post-war German-speaking migrants in Australia. While historical and societal changes have provided greater opportunities for German to be maintained as a heritage language in Australia, these developments may have come too late or have not been effective in the face of English as the dominant language in Australia and as a global language. Our investigation indicates that Australians with German as a heritage language, like many other migrant groups, are still at a high risk of shift to English, despite recent opportunities for language maintenance provided by modern society.